Prosedur Jasa Pengiriman Barang Pada PT. Wahana Prestasi Logistik - Eira Nabilah Rasyiqah Puteri; Sutini Sutini (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Goods delivery services do have an important role in economic growth, especially in goods transportation using airplanes. Transportation is getting better and developing fast and supported by advances in science and technology, now many domestic goods delivery companies have also been established. Where a company that delivers goods in its handling, apart from using sophisticated facilities and infrastructure, the company also needs cooperation with other parties to expand the company's network and performance system so that it can handle it better. Therefore, there is also a lot of competition between companies in the field goods delivery services in selling their products to consumers, but not everyone can set up a goods delivery company well, because to place a company in the domestic goods delivery services industry it must be able to have professional human resources, and high work standard capabilities. , if they want to get the best access to the market and the trust of consumers. This development has caused the emergence of many problems that must be immediately overcome by goods delivery service companies in order to maintain their business, especially to increase revenue in the sales function. These conditions cause companies to work hard to win the market, through a coordinated organizational structure, high specialization. , as well as the management's ability to work effectively and efficiently.